Reverse bias-dependence of schottky barrier height on silicon carbide: influence of the temperature and donor concentration - Latreche, Abdelhakim (International Journal of Physical Research, 2014)
The work deals with the dependences of the Schottky barrier height (SBH) on the reverse bias voltage, temperature and on donor concentration of metal/4H-SiC Schottky diodes. Using the tunneling modeling we have shown that the Schottky barrier height on silicon carbide strongly depends on the reverse bias voltage, temperature and doping concentration. At room temperature, the Schottky barrier height increases with increasing the reverse bias voltage at high doping concentration (about 1016 cm-3), while, at low doping concentration (about 1015 cm-3) the Schottky barrier height decreases with increasing the reverse bias voltage. These behaviors are independent of the Schottky barrier lowering effect. That means other effects occur at the barrier and depend on the reverse applied bias. The barrier height increases with increasing temperature and doping concentration under reverse bias conditions. The barrier heights extracted from the Padovani-Stratton formulas are close to the barrier heights extracted from the Tsu-Esaki formula in particular for the thermionic-field emission. Keywords: Extraction, Schottky Barrier Height, Reverse Bias, Tunneling, Silicon Carbide.